ELAZIĞ VE YAKIN ÇEVRESİNDEKİ TARİHİ CAMİLERİN MİMARİ YAPISI İLE SÜSLEMELERİNİN İNCELENMESİ - HAN, MEHMET VEFA (Fırat Üniveristesi, 2011)
Elazığ tarihi boyunca pek çok medeniyete ev sahipliği yapmıştır. Doğu-batı ve kuzey güney arasındaki geçiş yolu üzerinde bulunması, birbirinden farklı özellik gösteren medeniyetlerin izlerini taşımasına neden olmuştur. Bu etkiler mimari eserlere de yansımaktadır. Bu çalışmada camilerin mimari yapıları incelenmiştir. Bunun nedeni aynı amaçla inşa edilen yapıların zaman içerisinde göstermiş olduğu değişimi, incelemektir.Yapılan bu çalışmada Elazığ ve yakın çevresindeki camilerin mekânsal, yapısal ve süsleme özellikleri incelenmiştir. Böyle bir araştırma yapabilmek için, caminin ve cami ile ilgili olguların gelişim sürecinin incelenmesi gerekmektedir. Bu nedenle konu beş bölümde ele alınmıştır.İlk bölümde; cami mimarisin günümüze kadar değişimi anlatılmıştır. İkinci bölümde; cami yapılarının mekânsal kurgusu işlenmiştir. Üçüncü bölümde; yapıda kullanılan yapısal elemanlar tek tek ele alınmıştır. Dördüncü bölümde; yapıya estetik kazandıran süslemeler açıklanmıştır. Son bölümde; çalışmaya konu edilen camiler, mekân kurgusu, yapı elemanları ve süslemeleri incelenmiştir.

Elazığ has hosted many civilizations throughout history. Due to its place, which is between both east-west and north-south road, it contains many different civilization?s effects. These effects are also clearly seen in the architectural monuments. In this study architectural structure of the mosques is investigated. The reason of selecting this topic is to see the changes in the structure of the buildings during history.In this study the spatial, structural and ornamental characteristics of mosques in Elazığ and its close surrounding is investigated. To make such a study it is important to research how mosques and causes related to mosques have been developed in time. That is why the study part to be five chapters.In first chapter developing of architectural structure of the mosques form history to present were explained. In the second chapter spatial fiction structure of the mosques investigated. The third chapter is about materials used in the structure of mosques. These materials reviewed one by one. The ornament which gives aesthetic to the structure was explained in the chapter four. In the chapter five the spatial fiction structure, structural materials and ornaments of the mosques that searched about were investigated.
Investigation of architectural structure and decoration characteristics of structure material in Elaziğ and its close surround
Keywords: Mimarlık